2005
DOI: 10.1152/japplphysiol.01217.2004
|View full text |Cite
|
Sign up to set email alerts
|

Observations on force enhancement in submaximal voluntary contractions of human adductor pollicis muscle

Abstract: It has been observed consistently and is well accepted that the steady-state isometric force after active muscle stretch is greater than the corresponding isometric force for electrically stimulated muscles and maximal voluntary contractions. However, this so-called force enhancement has not been studied for submaximal voluntary efforts; therefore, it is not known whether this property affects everyday movements. The purpose of this study was to determine whether there was force enhancement during submaximal v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
91
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(110 citation statements)
references
References 44 publications
17
91
0
2
Order By: Relevance
“…For contractions performed without feedback of force or activation, as performed here, variations are likely greater than those found by Oskouei and Herzog (2005), as supported by the large standard deviations observed in the normalized data of Fig. 6.…”
Section: Residual Force Enhancementsupporting
confidence: 73%
See 1 more Smart Citation
“…For contractions performed without feedback of force or activation, as performed here, variations are likely greater than those found by Oskouei and Herzog (2005), as supported by the large standard deviations observed in the normalized data of Fig. 6.…”
Section: Residual Force Enhancementsupporting
confidence: 73%
“…Maximal voluntary contractions in human adductor pollicis under force and/or activation control have been associated with variations in force or activation of approximately 10% (Oskouei and Herzog 2005). For contractions performed without feedback of force or activation, as performed here, variations are likely greater than those found by Oskouei and Herzog (2005), as supported by the large standard deviations observed in the normalized data of Fig.…”
Section: Residual Force Enhancementsupporting
confidence: 67%
“…Common tasks, such as locomotion, typically involve short periods of activation during which muscle length and velocity vary continuously; however, this does not mean that rFE cannot play a role in such tasks. It has been shown that rFE is present almost immediately after the end of stretch (Edman et al, 1984), that isotonic as well as isometric force is enhanced (Edman et al, 1978), and that rFE occurs in muscles that are voluntarily activated to submaximal levels (Oskouei and Herzog, 2005). Therefore, it seems likely that rFE influences muscle force during everyday activities.…”
Section: Role Of Rfe In Vivomentioning
confidence: 99%
“…As in FD, the occurrence of FE initially was linked only to the lower limb and the peak of the LTC (22,23,24). However, new findings indicate that FE is also observed with reasonable stability in the ascending limb of the LCT (39,80,81,82).…”
Section: Theory Of Non-uniformity and Instability Of Sarcomerementioning
confidence: 77%
“…stimulation combined with maximum voluntary dynamic contractions (5). Furthermore, devices have relied on complex servo motors coupled to force transducers that bear little resemblance to human movement pattern (2,11,14,15,16,17,18,19,20,21,22,23,24,25,26).…”
Section: The Concept Of Force Depressionmentioning
confidence: 99%